Epithelial-Mesenchymal Transition in tumor microenvironment - Jing, Yingying (BioMed Central, 2011)
The epithelial to mesenchymal transition (EMT) plays crucial roles in the formation of the body plan and also in the tumor invasion process. In addition, EMT also causes disruption of cell-cell adherence, loss of apico-basal polarity, matrix remodeling, increased motility and invasiveness in promoting tumor metastasis. The tumor microenvironment plays an important role in facilitating cancer metastasis and may induce the occurrence of EMT in tumor cells. A large number of inflammatory cells infiltrating the tumor site, as well as hypoxia existing in a large area of tumor, in addition many stem cells present in tumor microenvironment, such as cancer stem cells (CSCs), mesenchymal stem cells (MSCs), all of these may be the inducers of EMT in tumor cells. The signaling pathways involved in EMT are various, including TGF-β, NF-κB, Wnt, Notch, and others. In this review, we discuss the current knowledge about the role of the tumor microenvironment in EMT and the related signaling pathways as well as the interaction between them.